2018
DOI: 10.1111/iep.12268
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of epidermal growth factor receptor and its downstream effector, focal adhesion kinase, correlates with papillary thyroid carcinoma progression

Abstract: Epidermal growth factor receptor (EGFR) and its downstream effector, focal adhesion kinase (FAK), have been shown to be overexpressed frequently in human malignancies and implicated in tumour aggressiveness. We aimed to investigate the relationship between EGFR and FAK expression and their possible correlation with the clinical phenotype of patients with papillary thyroid carcinoma (PTC). Expression profiles of EGFR and FAK were analysed in PTC tissue samples (n = 104) by immunohistochemistry and Western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
13
1
Order By: Relevance
“…Protein Phosphatase 2 Regulatory Subunit B"Alpha (PPP2R3A), also known as PR72/B"α2 or PR130/B"α1, belongs to the PP2A regulatory subunit B" family and has been found to regulate several important cancer‐related signaling pathways, such as the Wnt‐signaling cascade, epidermal growth factor (EGF)‐EGF receptor (EGFR) signaling, and the 5′ adenosine monophosphate‐activated protein kinase (AMPK) activity . In the recent years, these signaling pathways have been found to play essential roles, either via abnormal activation or inactivation, in the occurrence and development of liver cancer, through such functions as regulating cell adhesion ability, promoting an inflammatory environment, and enhancing cell proliferation, migration, and invasion . These findings imply a potential role for PPP2R3A in liver cancer, but considering its cellular context‐specificity, the function of PPP2R3A in liver cancer remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Protein Phosphatase 2 Regulatory Subunit B"Alpha (PPP2R3A), also known as PR72/B"α2 or PR130/B"α1, belongs to the PP2A regulatory subunit B" family and has been found to regulate several important cancer‐related signaling pathways, such as the Wnt‐signaling cascade, epidermal growth factor (EGF)‐EGF receptor (EGFR) signaling, and the 5′ adenosine monophosphate‐activated protein kinase (AMPK) activity . In the recent years, these signaling pathways have been found to play essential roles, either via abnormal activation or inactivation, in the occurrence and development of liver cancer, through such functions as regulating cell adhesion ability, promoting an inflammatory environment, and enhancing cell proliferation, migration, and invasion . These findings imply a potential role for PPP2R3A in liver cancer, but considering its cellular context‐specificity, the function of PPP2R3A in liver cancer remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…GO and KEGG enrichment analysis, establishment of PPI network and network topological analysis were utilized to identify genes potentially related to the initiation and development of PTC. It can be hypothesized that most of the DEGs identified in the present study were enriched in multiple cancer initiation and development-related pathological processes and signaling pathways based on GO and KEGG enrichment analysis from previous research (32)(33)(34)(35)(36)(37). Recent evidence from network biology suggests that genes and proteins do not function in isolation.…”
Section: Discussionmentioning
confidence: 66%
“…The results showed that the EGFR-related signaling pathways were enriched many times, which was similar to the results of the previous studies. Many reports believe that the high expression of EGFR is positively correlated with the progress of PTC [ 22 , 24 , 25 , 51 , 52 ]. And the activation of the EGFR signal pathway contributes to the development of EMT in tumor cells [ 27 , 28 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of epidermal growth factor receptor (EGFR) is associated with thyroid carcinoma progression [21]. Recent studies have found that the detection of EGFR expression in patients with PTC is helpful to judge the prognosis of patients with PTC [22][23][24][25]. In addition, EGF/EGFR signal pathway plays a crucial role in the EMT progression of thyroid cancer cells [26,27].…”
mentioning
confidence: 99%